The Essence of the Constitutional Requirement on the Establishment of Taxes, Duties, and other Mandatory Payments in Accordance with the Law - Badalyan, Sayad (Bulletin of Yerevan University C: Jurisprudence, 2025)
This article examines the constitutional and human rights dimensions of tax obligations in the Republic of Armenia, focusing on Article 60(8) of the 2015 Constitution, which integrates the obligation to pay taxes, duties, and other mandatory payments into the provision on the right to property. The analysis reveals a legal transformation: whereas previous constitutions treated taxation as a standalone civic duty, the 2015 Constitution reframes it as a legitimate restriction on property rights.Through a doctrinal analysis of Constitutional Court jurisprudence—particularly Decisions ՍԴՈ-753 (2008), ՍԴՈ-816 (2009), ՍԴՈ-1142 (2014), and ՍԴՈ-1436 (2018)—the article clarifies the principle of legality as applied to taxation. The Court has consistently ruled that both the types of taxes and their constituent elements (e.g., taxable base, rates, and scope) must be defined exclusively by law, not by sub-legislative acts.The article further compares Armenian constitutional standards to the European Court of Human Rights’ interpretation of Article 1 of Protocol No. 1 to the European Convention on Human Rights. It emphasizes that taxation, while an interference with property rights, is permissible when it is lawful, pursues a legitimate public aim, and satisfies the requirement of proportionality.A practical case study on cadastral valuation illustrates how delegating key components of tax determination (e.g., zoning boundaries) to government decisions violates the principle of legality and may lead to unconstitutional interference with property rights.Ultimately, the article concludes that to be valid, tax obligations must be clearly and comprehensively grounded in legislation, ensuring legal certainty, predictability, and compliance with constitutional and international human rights standards
Keywords: Tax obligations; Taxes; Duties; Mandatory payments; Principle of legality; Legal certainty; Right to property